La France : Les difficultés d’une réussite - Coulomb, Pierre; Delorme, Hélène (Études internationales, 1981)
Since 1970 the government brings differrenciated pressure to bear on production prices but this policy goes with the emergence of France as a big world food exporter. However since 1974 the instability of external trade and the sensible drop in agricultural income has led, 20 years after the i960's laws, to a new agricultural policy. Despite the large current debates, the definition of this new policy seems to have to await the post-crisis phase.